Comparison of traditional systemic analgesic, single shot or continuous fascia iliaca compartment block for pain management in patients with hip or proximal femoral fractures: A protocol for systematic review and network meta-analysis. - Jia-Xi Tang; Ling Wang; Shaojin Bu; Wallisa Roberts; Narcis Ungureanu; Ansar Mahmood; Fang Gao; Raja V Lakshmanan; Tonny Veenith; Rajneesh Sachdeva (PLoS ONE)
Introduction Pain management for hip and proximal femoral fractures includes oral and parenteral opioids and various regional anesthesia techniques. Fascia iliaca compartment blocks (FICB) are commonly used for these patients. At present, a unified view of the analgesic effect of FICB has not been reached. In addition, the comparison between single shot FICB and continuous FICB has not elicited clear evidence-based results. We will compare the efficacy and safety of systemic analgesics, single shot or continuous FICB in the pain management, complication prevention and satisfaction, in our systematic review and network meta-analysis. Methods China National Knowledge Infrastructure, Chinese Biomedical Literatures database, PubMed, the Cochrane Central Register of Controlled Trials, Physiotherapy Evidence Database, EMBASE, and Web of Science will be searched until June 2023. Two authors will independently screen the studies for eligibility and perform data extraction. The Cochrane risk of bias tool (RoB 2) will be used to assess the quality of evidence. We will use the GRADE approach to assess the certainty of the evidence across studies included in this review. All the statistical analyses will be conducted using Rev Man 5.3, WinBUGS 1.4.3, and Stata 13. Ethics and dissemination Our review involves a secondary analysis of existing published studies, therefore there is no need for formal research ethics approval. We will disseminate our findings through publication in a peer-reviewed journal. Protocol registration PROSPERO, CRD42023425282.